Answer :

Wolfyy

Steps to solve:

24(x - 1) = -6(4 - x) + 18

~Distribute

(24 * x) + (24 * -1) = (-6 * 4) + (-6 * -x) + 18

~Simplify

24x - 24 = -24 + 6x + 18

~Combine like terms

24x - 24 = -6 + 6x

~Add 24 to both sides

24x - 24 + 24 = -6 + 24 + 6x

~Simplify

24x = 18 + 6x

~Subtract 6 to both sides

24x - 6x = 18 + 6x - 6x

~Simplify

18x = 18

~Divide 18 to both sides

18x/18 = 18/18

~Simplify

x = 1

Best of Luck!

Hi1315

Answer:

[tex]x = 1[/tex]

Step-by-step explanation:

[tex]24(x - 1) = - 6(4 - x) + 18 \\ 24x - 24 = - 24 + 6x + 18 \\ 24x - 6x = 24 - 24 + 18 \\ 18x = 18 \\ \frac{18x}{18} = \frac{18}{18} \\ x = 1[/tex]

hope this helps

brainliest appreciated

good luck! have a nice day!

Other Questions